2016
DOI: 10.1021/acs.orglett.6b01089
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Aromatic N-Oxidation in the Biosynthesis of Phenazine Antibiotics from Lysobacter antibioticus

Abstract: Heterocyclic aromatic N-oxides often have potent biological activities, but the mechanism for aromatic N-oxidation is unclear. Six phenazine antibiotics were isolated from Lysobacter antibioticus OH13. A 10 gene cluster was identified for phenazine biosynthesis. Mutation of LaPhzNO1 abolished all N-oxides, while non-oxides markedly increased. LaPhzNO1 is homologous to Baeyer-Villiger flavoproteins but was shown to catazlye phenazine N-oxidation. LaPhzNO1 and LaPhzS together converted phenazine 1,6-dicarboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 34 publications
3
113
0
Order By: Relevance
“…Flavoenzymes play important roles in N-oxidations of natural products to introduce N -hydroxyl, 40 44 , 46 , 48 , 49 oxime, 50 54 nitro, 45 , 47 , 55 60 nitrone, 61 , 62 and nitrile functional groups. 63 , 64 In this study, XiaK was biochemically characterized as a FAD-dependent N -hydroxylase that catalyzes the conversion of XMA ( 1 ) into NOXM ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Flavoenzymes play important roles in N-oxidations of natural products to introduce N -hydroxyl, 40 44 , 46 , 48 , 49 oxime, 50 54 nitro, 45 , 47 , 55 60 nitrone, 61 , 62 and nitrile functional groups. 63 , 64 In this study, XiaK was biochemically characterized as a FAD-dependent N -hydroxylase that catalyzes the conversion of XMA ( 1 ) into NOXM ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the phenazine repertoire of L. antibioticus , as well as the specific genes responsible for their synthesis and modification, were recently characterized in depth. Specifically, the L. antibioticus gene products La PhzS and La PhzNO1 were shown to catalyze the decarboxylative hydroxylation and N-oxidations of PDC to generate the phenazine iodinin ( Zhao et al, 2016 ). In addition, the SAM-dependent O-methyltransferase, La PhzM, was later found to convert iodinin into the highly toxic phenazine, myxin ( Jiang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…UV-Vis and positive MS scans were acquired for each run. The known masses for phenazine previously detected in L. antibioticus ( Jiang et al, 2018 ; Zhao et al, 2016 ) were identified by comparing among WT, Δ phzT and Δ phzA cultures. Phenazine UV-absorbance was measured at 254 nm, 280 nm and 288 nm ( Figure 4—figure supplement 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the isolated enzymes, methane monooxygenase and cytochrome P450 as well as Rhodococcus jostii TMP1 cells have been shown to oxidize N ‐heterocycles with a presumed formation of N ‐oxides; however, further studies have not been elaborated. Other efforts to exploit enzymes or cells for the synthesis of N ‐oxides involved peroxygenase from Agrocybe aegerita , cyclohexanone monooxygenase from Lysobacter antibioticus , and whole cells of Verticillium sp . GF39 and Burkholderia sp .…”
Section: Introductionmentioning
confidence: 99%